2017
DOI: 10.1128/aac.02752-16
|View full text |Cite
|
Sign up to set email alerts
|

Activity of LCB01-0371, a Novel Oxazolidinone, against Mycobacterium abscessus

Abstract: Mycobacterium abscessus is a highly pathogenic drug-resistant rapidly growing mycobacterium. In this study, we evaluated the in vitro, intracellular, and in vivo activities of LCB01-0371, a novel and safe oxazolidinone derivative, for the treatment of M. abscessus infection and compared its resistance to that of other oxazolidinone drugs. LCB01-0371 was effective against several M. abscessus strains in vitro and in a macrophage model of infection. In the murine model, a similar efficacy to linezolid was achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 30 publications
0
45
0
Order By: Relevance
“…The MICs of the compounds were determined as described previously [26]. Briefly, 100 µL of cation-adjusted Mueller-Hinton (CAMH) and 7H9 broth supplemented with 10% ADC was added to every well of a 96-well microtiter plate.…”
Section: Minimum Inhibitory Concentration (Mic) Determination Using Rmentioning
confidence: 99%
“…The MICs of the compounds were determined as described previously [26]. Briefly, 100 µL of cation-adjusted Mueller-Hinton (CAMH) and 7H9 broth supplemented with 10% ADC was added to every well of a 96-well microtiter plate.…”
Section: Minimum Inhibitory Concentration (Mic) Determination Using Rmentioning
confidence: 99%
“…Finally, the oxazolidinone linezolid was also reported to synergize with rifabutin [83]. Unfortunately, linezolid's toxicity profile has limited its use in the clinic, but both tedizolid and LCB01-0371 have activity against M. abscessus and improved safety profiles [90,91]. While synergies between these oxazolidinones and rifabutin have not been determined in vitro, rifabutin addition improved the potency of the imipenemtedizolid combination against M. abscessus in a macrophage infection model [92].…”
Section: Partners In Crime: Harnessing Antibacterial Drug Synergiesmentioning
confidence: 99%
“…A recent meta-analysis revealed that more than 90% of MDR-TB cases achieved culture conversion after treatment with individualized regimens containing linezolid, underscoring the excellent in vivo efficacy of the drug against MDR-TB (5). Recently, the novel oxazolidinone delpazolid was developed to produce improved antibacterial activity and safety (14,15). In vitro studies and pharmacological evidence have indicated that this new agent is more active than linezolid against various Gram-positive bacteria (14); however, data regarding the in vitro activity of delpazolid against MDR-and XDR-TB are limited.…”
mentioning
confidence: 99%